ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN SURAT MASUK DAN SURAT KELUAR PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA JAMBI - Muchtar, Emilia; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2019)
Currently in the making or filing letters to the Department of Population and Civil Registrar of JambiCity there are still some obstacles such as making incoming mail reports, outgoing mail reports, recapreports, as well as when checking the report in certain period, searching documents that have been storedis still difficult and takes longer time because those old documents must be rechecked and reopened, andoftentimes the difficulty comes when we need to make a final recap of the report during a period whenthey are needed the most. Therefore, the author provide solutions in the form of information systemsmanagement to manage incoming and outgoing mail. This is helpful to facilitate employees in processingdata of incoming and outgoing mail and simplify the searching and the reports making processes. In thisresearch, the author uses UML (Unified Modeling Language) tool, Prototype model and VB.NETlanguage as a tool for making the design. In which the expected results are in the form of system designthat can make the searching and reports making processes easier and faster